A connexin43/YAP axis regulates astroglial-mesenchymal transition in hemoglobin induced astrocyte activation. Issue 10 (October 2018) - Yang, Yong; Ren, Jie; Sun, Yuhao; Xue, Yuan; Zhang, Zhijian; Gong, Aihua; Wang, Baofeng; Zhong, Zhihong; Cui, Zhenwen; Xi, Zhiyu; Yang, Guo-yuan; Sun, Qingfang; et al.
Abstract Reactive astrogliosis is a common response to insults to the central nervous system, but the mechanism remains unknown. In this study, we found the temporal and spatial differential expression of glial fibrillary acidic protein (GFAP) and Vimentin in the intracerebral hemorrhage (ICH) mouse brain, indicating that the de-differentiation and astroglial-mesenchymal transition (AMT) of astrocytes might be an early event in reactive astrogliosis. Further we verified the AMT finding in purified astrocyte cultures exposed to hemoglobin (Hb). Additionally, Connexin 43 (Cx43) downregulation and YAP nuclear translocation were observed in Hb-activated astrocytes. Knocking down Cx43 by siRNA triggered YAP nuclear translocation. Cx43 and YAP were physically associated as determined by immunofluorescence and co-immunoprecipitation. We propose that astrocytes undergo AMT during Hb-induced activation where Cx43 downregulation facilitates YAP nuclear translocation is a novel mechanism involved in this process. Cx43-YAP interaction may represent a potential therapeutic target for modulating astrocyte activation.